2020
DOI: 10.1016/j.ebiom.2020.103020
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signalling in fibro/adipogenic progenitors robustly enhances muscle regeneration

Abstract: Background During muscle regeneration, excessive formation of adipogenic and fibrogenic tissues, from their respective fibro/adipogenic progenitors (FAPs), impairs functional recovery. Intrinsic mechanisms controlling the proliferation and differentiation of FAPs remain largely unexplored. Methods Here, we investigated the role of retinoic acid (RA) signalling in regulating FAPs and the subsequent effects on muscle restoration from a cardiotoxin-induced injury. Blockage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 58 publications
(95 reference statements)
4
37
1
Order By: Relevance
“…Recently, this signaling was also explored also in the regeneration context focusing on FAP biology. Here, RA improves muscle regeneration upon acute injury and successfully limits FAP differentiation into adipocytes both in vitro and in vivo [69]. Specifically, exogenous addition of RA to FAP cultures halts their adipogenic differentiation [69] and pharmacological inhibition of RAR receptors reverts such inhibitory effect.…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, this signaling was also explored also in the regeneration context focusing on FAP biology. Here, RA improves muscle regeneration upon acute injury and successfully limits FAP differentiation into adipocytes both in vitro and in vivo [69]. Specifically, exogenous addition of RA to FAP cultures halts their adipogenic differentiation [69] and pharmacological inhibition of RAR receptors reverts such inhibitory effect.…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%
“…Specifically, exogenous addition of RA to FAP cultures halts their adipogenic differentiation [69] and pharmacological inhibition of RAR receptors reverts such inhibitory effect. Supplementation of RA stimulates FAP proliferation while facilitating FAP apoptosis during the remodeling stage [69]. Expression of conditional dominant negative Retinoic acid receptor alpha (RAR-alpha 403 ) in FAPs causes ectopic adipogenesis and impairs muscle regeneration [69].…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, deletion of FAPs cilia over-activates Hedgehog signalling and prevents adipogenesis following glycerol-induced muscle injury [ 36 ]. Another study indicated that retinoic acid receptor signalling plays an important role in the intrinsic regulation of FAPs number and cell fate decision [ 57 ]. Treatment of FAPs with retinoic acid promotes their proliferation in vitro and inhibits their adipogenic and fibrogenic differentiation both in vitro and in vivo (in obese mice fed with high-fat diet) [ 57 ].…”
Section: Faps In Skeletal Muscle Injury/regenerationmentioning
confidence: 99%